Genetic of Fertility Restoration of ‘WA’ Type Cytoplasmic Male Sterility in Rice - Raj, K. Govinda; Virmani, S.S. (Wiley, 1988)
Information on the genetics of fertility restoration in a cytoplasmic male sterility (CMS) system facilitates breeding and/or selection of restorer lines used in hybrid breeding programs involving CMS. Inheritance of fertility restoration of ‘WA’ type CMS in rice, (Oryza saliva L.) was studied utilizing two CMS lines in combination with five restorers. Each cross was used to develop a set of materials consisting of the following generations; parent lines (A, B, and R lines); (A/R) F1; (A/F1) BC1; (F1/B) BC2; and (A/R) F2. These materials were grown in the field setwise during 1985 to 1986. Results indicated that fertility restoration in all the restorers studied (‘IR26’, ‘IR36’, ‘IR54’, ‘IR9761‐19‐1’ and ‘IR2797‐105‐2‐2‐3’) was governed by two independent and dominant genes, and one of the genes appeared to be stronger in action than the other. The mode of action of the two genes varied in different CMS/restorer combinations revealing three types of interaction: epistasis with dominance (F2 ration, 12 fertile:3 partially fertile/partially sterile:1 sterile); epistasis with recessive gene action (F2 ratio, 9:3:4); or epistasis with incomplete dominance (F2 ratio, 9:6:1). The mode of interaction of the genes of a restorer differed with the CMS line used. An allelism test involving six R lines revealed that IR26 and IR36, and IR54 and IR9761‐19‐1 possessed identical restorer genes; ‘IR42’ and IR2797‐ 105‐2‐2‐3 had different restorer genes. Four groups of restorers with different pairs of restorer genes were identified. Testcross observations involving parental lines in the pedigree of IR36 and IR42 revealed that ‘Cina’, ‘Latisail’, ‘Tadukan’, ‘TN1’, ‘TKM 6’ and (two accessions) ‘PTB 18’ and ‘SLO 17’ are the probable original sources of R genes in the two restorer lines.